A Novel Quinoline Inhibitor of the Canonical NF-κB Transcription Factor Pathway - Panagiotis Ntavaroukas; Konstantinos Michail; Rafaela Tsiakalidou; Eleni Stampouloglou; Katerina Tsiggene; Dimitrios Komiotis; Nikitas Georgiou; Thomas Mavromoustakos; Stella Manta; Danielle Aje; Panagiotis Michael; Barry J. Campbell; et al. (Biology)
The NF-κB family of transcription factors is a master regulator of cellular responses during inflammation, and its dysregulation has been linked to chronic inflammatory diseases, such as inflammatory bowel disease. It is therefore of vital importance to design and test new effective NF-κB inhibitors that have the potential to be utilized in clinical practice. In this study, we used a commercial transgenic HeLa cell line as an NF-κB activation reporter to test a novel quinoline molecule, Q3, as a potential inhibitor of the canonical NF-κB pathway. Q3 inhibited NF-κB-induced luciferase in concentrations as low as 5 μM and did not interfere with cell survival or induced cell death. A real-time PCR analysis revealed that Q3 could inhibit the TNF-induced transcription of the luciferase gene, as well as the TNF gene, a known downstream target gene. Immunocytochemistry studies revealed that Q3 moderately interferes with TNF-induced NF-κB nuclear translocation. Moreover, docking and molecular dynamics analyses confirmed that Q3 could potentially modulate transcriptional activity by inhibiting the interaction of NF-κB and DNA. Therefore, Q3 could be potentially developed for further in vivo studies as an NF-κB inhibitor.